Módulo mujer en edad fértil: atención para la planificación familiar y la anticoncepción e ive. (2020)
This document presents information related to the process of activities carried out as a research assistant for the project entitled "Effectiveness of a knowledge management program on human talent in health for the implementation of the integrated route of care in maternal and perinatal health in the E.S.E. Integrated sub-network of health services in the South". This project seeks to contribute to the reduction of maternal mortality. Two pedagogical tools were designed as the articulating axis that explores knowledge of and adherence to the comprehensive care route in maternal and perinatal health. (G.I. Innovation & Care, 2019). It describes the contribution and assistance made as a researcher assistant, as well as the products presented. The contribution as a collaborator in the educational design is described, this pedagogical material was designed to carry out the educational sessions that complement the adoption of best practices in maternal-perinatal care. The related products are: Module Woman in Fertile Age: "Care for Family Planning and Contraception and IVE (Voluntary Interruption of Pregnancy)" booklet in PDF and digital format, using the application "Genially" which was adjusted in the Moodle software, Course: "RIAS Materno Perinatal", designed for the project. Due to the health emergency COVID19, it has not been possible to apply the theoretical and practical educational sessions. In addition, it was decided to continue the project by adapting the product to the context of the school classroom.